Banking in a Steady State of Low Growth and Interest Rates - Chen, Qianying (IMF Working Papers; Working Paper ;, 2018)
A prolonged low-interest-rate environment presents a significant challenge to banks and is likely to entail major changes to their business models over the long-run. Lower returns to maturity transformation in the face of flatter yield curves and an inability to offer deposit rates significantly below zero combine to compress bank earnings in this environment. Smaller, deposit-funded, less diversified banks are hurt most, increasing consolidation pressures and reach-for-yield incentives, presenting new financial stability challenges.To the extent that such an economic environment reflects a new, steady-state with lower equilibrium growth driven by population aging and slower productivity growth, lower credit demand is likely to drive banking toward provision of fee-based, utility services.